The impact of demographic variables on the formation of propaganda and its reflection on fabric and fashion designs (Journal of the College of Basic Education, 2026)
Demographic variables have become a fundamental element upon which designers rely in creating artistic products. This change has helped highlight specific individual characteristics, moving away from the principle of partnership and the language of dialogue between two parties. As a result, some companies and designers have been able to deal with modern demographic characteristics, which has revealed the one-sided nature of these designs (propaganda) for a specific group, without involving the recipient's environment and culture. This lack of compatibility between the designer and the recipient has resulted in these designs conveying specific cultures to some societies, according to the principle of comprehensive dissemination. This has resulted in different behaviors within the concept of change in population characteristics (demographic change), which has helped convey certain characteristics without waiting for feedback from the user environment. Therefore, the current research aims to understand the acceptance and effects of these design products on the user environment. Therefore, the first chapter presents the research problem, which is: "To what extent do demographic variables influence the formation of propaganda, especially in textile and fashion designs, and the transition from privacy to publicity?" It also includes the importance of the research, its objectives, its limitations, and the definition of terminology. Chapter Two comprises multiple axes that contributed to defining the research form and analyzing the models within Chapter Three. The researcher presented the research results in Chapter Four, the most prominent of which are : 1-The designer relied on familiar forms that held a special sanctity in the recipient's mind, which later helped transition the design models to unfamiliar formalities. These models formed propaganda with a specific ideology that addressed a specific category of recipients and excluded others from the design concept, creating a unipolar dialogue. 2-The change in population characteristics contributed to the creation of unilateral design outcomes, relying on the emotional aspect as a result of the oppression present in some societies. This led to achieving inclusiveness and communicating the design concept to recipients from alien cultures. The conclusions, recommendations, proposals, and sources were then presented.